EXTENDED MODELLING AND NUMERICAL INVESTIGATION OF PHASED ARRAY SYNTHETIC JET CROSS-FLOW INTERACTIONS - Sidra Malik; T.M. Shah; N. Kousar; Zahir Hussain (European Scientific Journal, ESJ, 2015)
A classical analysis of incompressible unsteady Navier-Stokes equation have been under discussion for a long time by various reasearchers, it has been found that the exact analytical unique solution existed only below and undefined Reynolds number limit. Several solutions were existed for a range of Reynolds number above the limit, and that has no solution exsisted above the second undefined Reynolds number (i.e, solution enter into turbulent region and one has to solve another set of equations for turbulance). A useful study was done for two dimensional unsteady incompressible flow in which vorticity is propotional to stream function perturbed by uniform stream. Recently this unsteady sloution was used to analyse the flow behaviour on flat plate using Synthetic Jet Actuators (SJA) which consists of oscillating membrane expels in fluid through orifice. The results obtained at different time level were presented and it was found as the time progresses streamlines, on the flat plate with number of actuators placed in an array, become flatter caused rapidly decay in vortices on trailing edge. The authentication of these results were needded to be validated through experiment or numerical simulation. In this paper, an attempt has been made to solve incompressible unsteady Navier-Stokes equations numerically to analyse the behaviour of single and multiple sythetic jet actuator in a cross flow conditions. The behaviour of SJA implemented by imposing a special kind of boundary condition on the bottom of flate plate was studied. Results have been obtained for various Reynolds numbers and were presented. These numerical results were in close agreement with [1].